The effect of Ocimum basilicum and Cuminum cyminum seeds on the weight gain and rumen activity and fermentation in Awassi rams - Dawood, Tamara N. (The Iraqi Journal of Veterinary Medicine, 2014)
This study was carried out at Animal Farm, College of Veterinary Medicine, Baghdad University from April up to July 2013. The animals were fed on concentrate diet and freely grazed for 3-6 hours/ day at College Field, rams were used in a Latin square design (4*4) and trans located biweekly intervals, respectively to different concentrate diets, the first diet 2% of the body weight which was free from any addition and considered as a control, the second diet was contain 3% Cuminum cyminum seeds (CU), while the third diet was contain 3% of Ocimum basilicom seeds (B) and the fourth concentrated diet was contain 1.5% of Cuminum cyminum and 1.5% Ocimum basilicom seeds (CU+B). Results revealed that there was significant (P<0.05) difference existed during the first two periods in the body gain compared with other periods, pH of rumen liquor of the control group 6.00±0.24 showed significantly (P<0.05) higher than all other animals during all periods 5.42±0.095, 5.40±0.14 and 5.65±0.11, while the volatile fatty acids were significantly lower in the control animal 8.25±0.75 compared with other animals, ammonia concentration in the rumen liquor, showed higher significant (P<0.05) difference 9.33±0.13 and 9.60±0.43 respectively in the third and fourth period than first period 7.52±0.28, on the other hand bacterial count of the control group was significantly (P<0.05) lower than other groups.